#djlife During the Pandemic: Reflections from DJs Rearranging Relations and Improvising Continuity - Campbell, Mark V.; Barut, Ayse (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
This piece profiles two DJs who moved online during the pandemic and discusses the restrictions placed by social media companies around certain modes of music making on their platforms. Hip hop DJs in particular have been scrutinized by many social media outlets for playing copyrighted music as part of their DJ sets.